Family Management of Pediatric Cancer: Links with Parenting Satisfaction and Psychological Distress. Issue 3 (31st July 2018) - Salvador, Ágata; Crespo, Carla; Barros, Luísa
Abstract : Research has long acknowledged the disruptions posed by pediatric cancer diagnosis and treatment to family life. Nonetheless, the mechanisms through which the family response influences parents' mental health in this adverse context are not fully understood. The main goal of the present study was to examine the direct and indirect links, via parenting satisfaction, between family condition management and psychological distress of parents of children with cancer. Participants were 201 parents (86.6% mothers) of children/adolescents diagnosed with cancer who completed self‐report questionnaires assessing family condition management (family life difficulty and parental mutuality), parenting satisfaction, and psychological distress (anxiety and depression). Structural equation modeling was used to test the proposed mediation model. The results showed that parenting satisfaction mediated the association between both the family condition management dimensions (family life difficulty and parental mutuality) and depression. Specifically, greater family life difficulties and lower parental mutuality were associated with lower parenting satisfaction, which, in turn, was associated with higher levels of depression. Additionally, greater family life difficulties and lower parental mutuality were directly linked to higher levels of anxiety. Multigroup analyses suggested that the model was valid across patient age groups (children vs. adolescents) and treatment status (on vs. off‐treatment). These findings reinforce the need for family‐ and parent‐based interventions in the pediatric oncology field. Interventions that target families' difficulties and promote their resources are likely to foster parenting satisfaction and psychological adjustment. Abstract : Desde hace tiempo, las investigaciones han reconocido las dificultades que plantea el diagnóstico de cáncer infantil y el tratamiento para la vida familiar. No obstante, los mecanismos a través de los cuales la respuesta de la familia influye en la salud mental de los padres en este contexto adverso no se comprenden totalmente. El objetivo principal del presente estudio fue analizar los vínculos directos e indirectos, mediante la satisfacción con la crianza, entre el manejo de la enfermedad por parte de la familia y el distrés psicológico de los padres de niños con cáncer. Los participantes fueron 201 padres (86.6% madres) de niños/adolescentes diagnosticados con cáncer quienes contestaron cuestionarios de autoinforme que evaluaban el manejo de la enfermedad por parte de la familia (la dificultad para la vida familiar y la reciprocidad parental), la satisfacción con la crianza y el distrés psicológico (ansiedad y depresión). Se utilizó el modelo de ecuaciones estructurales para evaluar el modelo de mediación propuesto. Los resultados demostraron que la satisfacción con la crianza medió la asociación entre las dimensiones de manejo de la enfermedad por parte de la familia (la dificultad para la vida familiar y la reciprocidad parental) y la depresión. Específicamente, una mayor dificultad para la vida familiar y una menor reciprocidad parental estuvieron asociadas con una menor satisfacción con la crianza, la cual, a su vez, estuvo asociada con niveles más altos de depresión. Además, una mayor dificultad para la vida familiar y una menor reciprocidad parental estuvieron asociadas directamente con niveles más altos de ansiedad. Los análisis multigrupo sugirieron que el modelo era válido entre los grupos etarios de pacientes (niños frente a adolescentes) y el estado del tratamiento (en tratamiento frente a sin tratamiento). Estos hallazgos reafirman la necesidad de realizar intervenciones para la familia y los padres en el ámbito de la oncología pediátrica. Probablemente, las intervenciones que se ocupen de las dificultades de las familias y promuevan sus recursos fomentarán la satisfacción con la crianza y la adaptación psicológica. Abstract : 研究很早就承认了儿科癌症诊断和治疗对于家庭生活的干扰. 然而家庭反应如何在这一不良背景下影响家长心理健康的机制还没有被完全理解.该研究的主要目的是通过亲职满意度考察家庭情况管理和患有癌症儿童家长的心理困扰之间的联系.参与者为201名被诊断患有癌症的儿童/青少年的家长(86.6% 是母亲).这些参与者完成了评估家庭情况管理(家庭生活困难和家长相互性)自我报告问卷, 亲职满意度以及心理困扰(焦虑和抑郁).我们使用结构性等式模型来测试所提出的调和模型.研究结果显示亲职满意度调节家庭情况管理维度(家庭生活困难和家长相互性)以及抑郁之间的关联. 特别是, 较多的家庭生活困难和较低的家长相互性和较低的亲职满意度相关, 而较低的亲职满意度又和较高的抑郁水平相关.此外, 较多的家庭生活困难和较低的家长相互性直接和较高水平的焦虑相关.多小组分析显示该模型在不同患者年龄组(儿童和青少年)和治疗状况都适用.这些发现增强了儿科肿瘤领域对于以家庭和家长为基础的干预措施的需求.针对家庭困难并促进其资源的干预措施可能促进亲职满意度和心理调适.